Chondrogenic differentiation of murine embryonic stem cells: effects of culture conditions and dexamethasone. - Tanaka, H; Murphy, C; Murphy, C; Kimura, M; Kawai, S; Polak, J (2004)
Pluripotent embryonic stem (ES) cells have the capability to differentiate to various cell types and may represent an alternative cell source for the treatment of cartilage defects. Here, we show that differentiation of ES cells toward the chondrogenic lineage can be enhanced by altering the culture conditions. Chondrogenesis was observed in intact embryoid body (EB) cultures, as detected by an increase in mRNA levels for aggrecan and Sox9 genes. Collagen IIB mRNA, the mature chondrocyte-specific splice variant, was absent at day 5, but appeared at later time points. Dexamethasone treatment of alginate-encapsulated EB cultures did not have a strong chondrogenic effect. Nor was chondrogenesis enhanced by alginate encapsulation compared to simple plating of EBs. However, disruption of day 5 EBs and culture as a micromass or pelleted mass, significantly enhanced the expression of the cartilage marker gene collagen type II and the transcription factor Sox9 compared to all other treatments. Histological and immunohistochemical analysis of pellet cultures revealed cartilage-like tissue characterized by metachromatically stained extracellular matrix and type II collagen immunoreactivity, indicative of chondrogenesis. These findings have potentially important implications for cartilage tissue engineering, since they may enable the increase in differentiated cell numbers needed for the in vitro development of functional cartilaginous tissue suitable for implantation.